Applying Qualitative Methods to Investigate Social Actions for Justice Using Social Media: Illustrations From Facebook. (June 2020) - Orth, Zaida; Andipatin, Michelle; Mukumbang, Ferdinand C; van Wyk, Brian
Social media is becoming a valuable resource for hosting activism as illustrated in the rise of the hashtag movements, such as #MeToo and #Endrapeculture, used to speak out against rape culture. In this article, we discuss the use of social media as the source and object of research, using the case of the 2016 South African #nakedprotest. We used naturalistic observation on Facebook comment threads and followed these up with online Facebook focus groups. Qualitative content analysis and thematic decomposition analysis were used, respectively, to explore online discourses of rape culture. We found that the use of social media as a medium for data collection is valuable for exploring trending social issues such as the rape culture #nakedprotest. We uncovered that social media offers researchers the opportunity to collect, analyze, and triangulate rich qualitative data for the exploration of social phenomena. This study illustrates the usefulness of social media as a pedagogical instrument.